Analysis of Items in the Mid-Semester Assessment of Science Class VII SMP Yapis Manokwari - Prayetno, Eko; Yusuf, Irfan; Mujasam, Mujasam (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2022)
The purpose of this study was to analyze the test items in the midterm assessment using the Rasch model in terms of validity, reliability, level of difficulty, discriminating power, and the effectiveness of distractors in class VII science questions at SMP Yapis Manokwari. This research is a quantitative research that uses descriptive quantitative methods with data collection techniques using documentation. Respondent data were 60 students with purposive sampling. The items used in the Mid Semester Assessment are 40 questions. From the validity test, it was found that the suitability level of the items was 35 questions that were fit and 5 questions that were not fit. Student reliability 0.81 means good, item reliability item 0.92 means very good and reliability between students with item 0.83 means special. The level of difficulty of the questions is in the medium category, which means that the questions are good. The discriminating power of the items obtained is that 2 items (5%) are in the very good category, 30 items (75%) are in the good category, 4 items (10%) are in the sufficient category, and 4 items (10%) are bad category, from the items it has succeeded in identifying the distinguishing power of students divided into 3 groups in the category of above average ability, average ability, and below average ability. The effectiveness of the distractor of the 40 questions in the test generally functions well. The conclusion is that the analysis of the items using the Rasch model in the midterm assessment is stated to be valid, reliable, the level of difficulty of the items is very good, the discriminating power is very good, and the effectiveness of the distractors obtained is in the good category.